Anti-oxidative and anti-inflammatory effects of lipoic acid in rat liver - Anna Goraca (Postępy Higieny i Medycyny Doświadczalnej, 2015)
Introduction: Lipopolysaccharide (LPS) is a key inflammatory component of Gram-negative bacteria, which after entering the systemic circulation contributes to the development of septic hepatic failure.Aim: The aim of this study was to evaluate the effects of alpha lipoic acid (LA) on oxidative stress parameters and inflammation in endotoxemic rat liver.Material/Methods: Male Wistar rats were divided into 4 groups, each group consisting of 8 animals. Group I received saline and served as a control, Group II received a single dose of LA (60 mg/kg i.v.), Group III received lipopolysaccharide (LPS) (15 mg/kg i.v.), and Group IV received LPS (15 mg/kg i.v.) and 30 min later received LA (60 mg/kg i.v.). Five hours after LPS or LA administration, the animals were sacrificed and the liver was isolated for measurements of levels of thiobarbituric acid reactive substances (TBARS), hydrogen peroxide (H2O2), total sulfhydryl groups (-SH), total glutathione (tGSH) and reduced glutathione (GSH).Results: Injection of LPS caused a significant increase in liver TBARS and H2O2 levels and a significant decrease in levels of -SH groups, tGSH and GSH. LPS-treated rats also showed an increase in TNF-α and IL-6 levels and edema in the liver. The administration of LA to endotoxemic rats significantly reduced TBARS, H2O2, TNF-α, and IL-6 levels and reduced edema in the liver when compared to the LPS group. This antioxidant also resulted in an increase in -SH groups and tGSH and GSH levels and ameliorated the glutathione redox status when compared to the LPS group.Conclusions: The results indicated that LA administered 30 min following LPS infusion may effectively prevent oxidative stress and inflammation in the liver. Thus LA is a potent antioxidant that can be useful in rebuilding LPS-induced damaged liver tissue.